(NsO^INENIQ(B: [1880-1882] /s (N~ASTX (B1s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B:s (NnAUKA(B,s, 1974)
(Nw (B1 (NTOM SOBRANIQ SO^INENIJ a(B.(Np(B. (N~EHOWA WO[LI RASSKAZY I @MORESKI NAPISANNYE (B1880-1882 (NGG(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (N`MORESKIs